AN INVESTIGATION INTO THE EFFECTS OF SCHEMATA ACTIVATION ACTIVITIES ON L2 LISTENING COMPREHENSION = NGHIÊN CỨU VỀ ẢNH HƯỞNG CỦA NHỮNG HOẠT ĐỘNG KÍCH THÍCH KIẾN THỨC NỀN TRONG VIỆC NGHE HIỂU NGÔN NGỮ THỨ HAI - Trần, Minh Thảo (2020)
This research project investigates the effects of using text-relevant schemata activation activities on listening comprehension of EFL sophomores of University of Languages and International Studies. The research subjects were divided into three groups, two receiving an experimental treatment (either formal or content schemata) and a control group receiving no treatment. At the end of treatment, a listening test including a summary writing task and a set of comprehension questions was administered to all groups. The analysis of the test scores revealed that the formal and content schemata activation activities significantly facilitated learners’ L2 listening comprehension. Between these two listening supports, the former brought about a slightly better listening outcome than the latter. Additionally, question types and learners’ general listening proficiency were two factors that moderated the effects of schemata activation on L2 listening comprehension. Learners performed greater on global questions than local question and high proficiency learners were found to benefit more from the formal schemata activation activities than low level counterparts. Regarding the pedagogical implications, this study informs teachers and course designers in their decision-making to select and/or design suitable pre-listening activities to foster learners’ listening comprehension.